2012
DOI: 10.1080/10640266.2012.668484
|View full text |Cite
|
Sign up to set email alerts
|

What Components of Perfectionism Predict Drive for Thinness?

Abstract: Perfectionism and drive for thinness have both been described as predictors of eating disorders, but the relationship between these two constructs over time requires further investigation, as does the an understanding of what components of perfectionism are important in this relationship. Using a longitudinal design, a population of 175 young adults was followed up over a 4 month period. Structural equation modelling indicated a unidirectional relationship between evaluative concerns and drive for thinness, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
2
11
2
1
Order By: Relevance
“…Evidence has indicated that there is a relationship between eating disorder symptoms and perfectionism, which is considered one of the personality traits related to eating disorder symptoms [15][16][17][18] . However, to date, no concrete evidence was presented in Brazilian literature.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Evidence has indicated that there is a relationship between eating disorder symptoms and perfectionism, which is considered one of the personality traits related to eating disorder symptoms [15][16][17][18] . However, to date, no concrete evidence was presented in Brazilian literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is noteworthy that according to some authors 19 , there are cultural differences regarding the emphasis on body type between different geographical locations, which can lead young people to have an increased or attenuated frequency of adopting eating disorder symptoms. Thus, although research in other countries [15][16][17][18] has indicated a positive relationship between perfectionism and eating disorder symptoms, there is a possibility that this association may not be true for the Brazilian context. Moreover, it is worth noting that much of this research was performed exclusively with women 15,18 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations